Mechanisms of yeast prion propagation - Tuite, Mick (Henry Stewart Talks, 2008)
Prions as infectious amyloids, Yeast [PSI+] prion and Sup35p, Molecular chaperone Hsp104, Guanidine hydrochloride as a prion propagation inhibitor, Propagons, Estimating propagon numbers using a stochastic model, Generation of new propagons, Propagation-defective mutants (PNM), Role of primary sequence information, Yeast prion propagation: the unanswered questions
Archived at 2021/02/25